2005
DOI: 10.1002/cncr.21367
|View full text |Cite
|
Sign up to set email alerts
|

Is BRCA1/BRCA2‐related breast carcinogenesis estrogen dependent?

Abstract: Estrogen is a well known promoting factor of sporadic breast carcinoma. With T he cumulative risk of breast carcinoma in carriers of BRCA1/ BRCA2 mutations ranges from 45% to 84% by age 70 years. 1,2Knowledge of carcinogenesis and promoting factors that modulate the risk of breast carcinoma in BRCA1/BRCA2 mutation carriers, thus, is essential for preventive decision making.Estrogens play a crucial role in the growth of normal and tumor mammary cells. There are data emerging from clinical studies showing that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 45 publications
2
11
0
6
Order By: Relevance
“…In support of this, it has been shown that premenopausal oophorectomy exerts an B50% reduction of the risk of breast cancer in BRCA1 mutation carriers (Rebbeck et al, 1999). Also, adjuvant antiestrogenic tamoxifen therapy resulted in a decreased risk of second primary carcinomas and an improved overall survival of BRCA mutation carriers (Metcalfe et al, 2004;Noruzinia et al, 2005).…”
Section: Validation Studiesmentioning
confidence: 88%
“…In support of this, it has been shown that premenopausal oophorectomy exerts an B50% reduction of the risk of breast cancer in BRCA1 mutation carriers (Rebbeck et al, 1999). Also, adjuvant antiestrogenic tamoxifen therapy resulted in a decreased risk of second primary carcinomas and an improved overall survival of BRCA mutation carriers (Metcalfe et al, 2004;Noruzinia et al, 2005).…”
Section: Validation Studiesmentioning
confidence: 88%
“…These data contrast with the fact that sporadic breast tumors are ER-positive (Noruzinia et al, 2005). The correlation between BRCA1 mutation and ER-negative breast cancer is an intrinsic property of BRCA1 cancers and not a consequence of the young age of onset or the tumor with high histological grade (Foulks et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…L'information donné e par le mé decin et la dé cision de la femme atteinte doivent inté grer au mieux ces diffé rents facteurs : -la demande de la malade, elle-mê me lié e à la perception du risque ; -repré sentation de la maladie par l'histoire familiale (nombre de cas de cancers, proximité des personnes atteintes, dé cè s) ; -le contexte personnel (â ge, enfants, situation familiale, chimiothé rapie) ; -le type de chirurgie du sein atteint (mastectomie ou conservation possible) ; -le caractè re invasif ou non de la tumeur ; -l'espé rance de vie et le pronostic du cancer du sein (estimé au mieux aprè s le geste chirurgical) ; -les traitements associé s pouvant avoir une efficacité pré ventive (tamoxifè ne, inhibiteur de l'aromatase chez les femmes mé nopausé es, chirurgie pré mé nopausique des annexes) [124] ; -les conditions de reconstruction mammaire immé diate uni-ou bilaté rale ; -le poids et la morphologie (dé sir de symé trie, plastie ré duction, obé sité ) ; -un anté cé dent d'irradiation ; -le type de pré disposition gé né tique (BRCA1, BRCA2 ou un trè s haut risque familial).…”
Section: Mastectomie Controlaté Raleunclassified
“…-une pré vention du carcinome ovarien indiqué e aprè s 40 ans ; -une pré vention mammaire en pré mé nopause [124] ; -une hormonothé rapie adjuvante lorsque la femme n'est pas mé nopausé e et que les RE sont positifs ; l'obtention du statut des RE par une biopsie est donc né cessaire à l'é valuation de l'aspect adjuvant de la suppression ovarienne en pré mé nopause.…”
Section: Annexectomie Bilaté Rale (Accord D'experts)unclassified